2007
DOI: 10.1148/radiol.2432060493
|View full text |Cite
|
Sign up to set email alerts
|

Intraaxial Brain Masses: MR Imaging–based Diagnostic Strategy—Initial Experience

Abstract: An integrated MR imaging-based strategy, which is accurate in differentiation of several intraaxial brain masses, was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
118
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(127 citation statements)
references
References 45 publications
7
118
0
2
Order By: Relevance
“…In a previous study, ADC was 90% accurate and 100% specific in differentiating between lymphomas and GBMs. 27 Our results agree with those of the previous report. The high specificity and accuracy of ADC in differentiating lymphoma from GBM are probably due to the differences in tumor cellularity, which has been considered the primary determinant of ADC.…”
Section: Discussionsupporting
confidence: 94%
“…In a previous study, ADC was 90% accurate and 100% specific in differentiating between lymphomas and GBMs. 27 Our results agree with those of the previous report. The high specificity and accuracy of ADC in differentiating lymphoma from GBM are probably due to the differences in tumor cellularity, which has been considered the primary determinant of ADC.…”
Section: Discussionsupporting
confidence: 94%
“…The AUC remained at about the same level as that in all the cases. This finding was in accordance with several previous studies 5,12,17 and indicates that the model is very helpful for readers, even for experienced radiologists.…”
Section: 36supporting
confidence: 93%
“…Restricted water diffusion in solid tumors has been reported by many groups. 7,[14][15][16][17] It is generally assumed that a solid tumor does not have any microstructural orientation by itself and its growth induces structural disorder in the tissue, which leads to decreased FA. 18 However, although the association between FA and tumor cellularity has been studied, the relationship remains unclear because both positive 12,14,19 and negative 16 correlations have been reported.…”
mentioning
confidence: 99%
“…1,[6][7][8][9] The ADC value, measured from diffusion-weighted imaging or DTI, has been reported to be inversely correlated with cellularity in tumors. 7,8 Prior studies have shown that ADC can help differentiate PCLs from high-grade gliomas 1,[6][7][8]10 and brain metastases 8 ; however, other studies have reported a substantial overlap between these tumor types. 11,12 DTI also provides diffusion anisotropy information about the tissue, such as FA, CL, CP, and CS.…”
mentioning
confidence: 99%